2014
DOI: 10.2147/cia.s73985
|View full text |Cite
|
Sign up to set email alerts
|

Cayenne aspiration: an unusual type of lower airway foreign-body aspiration

Abstract: PurposeCayenne aspiration is an unusual type of foreign-body aspiration that is usually misdiagnosed. This article analyzes the clinical features of cayenne aspiration in the lower airway.Patients and methodsClinical data on eight adult patients with cayenne aspiration were retrospectively analyzed. Six were elderly patients. The data were collected from Peking University First Hospital and Anhui Chest Hospital between January 2010 and August 2014.ResultsThe most common symptoms of cayenne aspiration were coug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 16 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…The diagnosis in this child was delayed for about 72 hours after admission. Delays in diagnosis have also been reported by various authors, and the duration of delay may be as long as 1 to 6 years [7,8].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The diagnosis in this child was delayed for about 72 hours after admission. Delays in diagnosis have also been reported by various authors, and the duration of delay may be as long as 1 to 6 years [7,8].…”
Section: Discussionmentioning
confidence: 74%
“…Even CT may produce a false negative result in the presence of a foreign body depending on the physical properties of the aspirated material and the slice thickness relative to the size of the foreign body. Therefore, direct visualization of the airways by bronchoscopy is advocated [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some geriatric patients do not have cough or lack the cognitive capacity to inform of an episode of FBA. Lin et al reported that only 29% of geriatric patients can declare an event of aspiration [ 4 ]. Furthermore, the asymptomatic period from the timing of aspiration can be longer than the following symptomatic period [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Others include iatrogenic objects such as endodontic needles, tracheostomy tube segments, endotracheal tube appliances, and miscellaneous items such as thumbtacks, pins, rivets, etc [13] . Among them, a few foreign bodies such as coins, nails, and teeth are radiopaque, thus they appear hyperdense in computed tomography (CT) scan and can be easily detected and identi ed [8,[14][15][16] . However, most organic foreign bodies are radiolucent and are unlikely to be detected directly by chest CT [8,12,15,17] .…”
Section: Introductionmentioning
confidence: 99%